In vitro propagation of Stephania pierrei diels and exploration of its potential as sustainable phytochemical production from tuber and callus - Chanakan Laksana; Onsulang Sophiphun; Somsak Nualkaew; Sontichai Chanprame (BMC Plant Biology)
Abstract Background The tuber of Stephania pierrei Diels has been used for treating cardiovascular disease, migraine, and body edema and may exhibit antimalarial, anticancer, and anticholinesterase properties. It is also a popular ornamental plant. Consequently, plant tubers have been extensively harvested from the wild, posing a high risk of extinction. We assessed the in vitro propagation and essential phytochemical production from the calli of S. pierrei. Results The highest callus weight (1.52–1.59 g) induced from the tuber flesh without peel occurred when using Murashige and Skoog (MS) medium with basal salts supplemented with 3–4 mg/L benzyladenine (BA) and 0.1 or 0.5 mg/L naphthaleneacetic acid. MS medium with a concentration of 3 mg/L BA was the most efficient medium for shoot regeneration, producing an average of 7.40 ± 1.140 shoots. Similarly, MS medium with 1 mg/L meta-topolin (mT) was most efficient for multiple shoot production (with an average of 13.40 ± 2.30 shoots). Root induction was successfully performed using the ½ MS medium. HPLC analysis revealed that calluses, tubers without peel, tubers with peels, and peels contained fangchinoline, cepharantine, and tetrandrine. Peels had the highest amounts of the first two alkaloids and a high amount of tetrandrine, which was related to the relative expression levels of three genes involved in the isoquinoline alkaloid biosynthesis pathway: coclaurine N-methyltransferase (CNMT), norcoclaurine synthase (NCS), and 6-O-methyltransferase (6OMT). GC–MS was employed for phytochemical identification of callus and tuber with peel, which revealed that out of the 24 phytochemicals identified, 13 were only found in callus and 5 were present only in tubers. DPPH scavenging percentage, ferric reducing antioxidant power, and ABTS radical cation scavenging activity assays revealed that the extracts from the four tissues showed antioxidant activities. The peel showed significantly higher total flavonoid and phenolic content, whereas the callus displayed the highest total alkaloid concentration. Conclusions Producing secondary metabolites such as cepharantine, tetrandrine, and fangchinoline by culturing callus holds potential as a low-cost and sustainable method for producing pharmaceutical phytochemicals.